Down-regulation of CXCL1 inhibits tumor growth in colorectal liver metastasis - Bandapalli, Obul Reddy; Ehrmann, Franziska; Ehemann, Volker; Gaida, Matthias; Macher-Göppinger, Stephan; Wente, Moritz N.; Schirmacher, Peter; Brand, Karsten (Cytokine, 2012)
As part of ongoing studies to obtain a global picture of invasion related events in colorectal liver metastases, here, we report our findings on gene expression of the pro-angiogenic subgroup of chemokines, the CXCL-ELR+ chemokines. Apart from their pro-angiogenic and chemoattractant function, these chemokines appear to also contribute to tumor cell transformation, growth and invasion. In our nude mouse model of colorectal liver metastases, we found CXCL1,2,3,5 and 8 (IL-8) to be up-regulated in the tumor cells of the invasion front as compared to the tumor cells in the inner parts of the tumor. ShRNA mediated down-regulation of the most prominently up-regulated group member, CXCL1/gro-alpha resulted in inhibition of cell viability, invasion and proliferation. In vivo, down-regulation of CXCL1 resulted in a nearly complete prevention of tumor growth in nude mice. Mechanistically, auto-regulatory mechanisms involving NF-kappaB and Akt appear to be involved in pro-tumorigenic functions of CXCL1.